Canine distemper virus increased the differentiation of CD4+CD8+ T cells and mRNA expression of inflammatory cytokines in peripheral blood lymphocyte from canine. (June 2019) - Song, Ke; Wu, Zong-Mei; Peng, Lu-Yuan; Yuan, Meng; Huang, Jiang-Ni; Zhang, Chun-Lei; Fu, Ben-Dong; Yi, Peng-Fei; Shen, Hai-Qing
Abstract: Background: Canine distemper virus (CDV) can cause a highly contagious disease to canid. However, how CDV affects peripheral blood lymphocyte (PBL) remains unclear. Methods: In this study, CDV infected PBL was cultured to investigate the effect of CDV on the differentiation of lymphocytes and the mRNA expression of inflammatory cytokines in PBL. Results: The results showed that CDV changed the phenotype of lymphocytes and increased the percentage of CD4 + CD8 + T cells. To explore the effect of immune response of lymphocytes to CDV, the mRNA expression of pro- and anti-inflammatory cytokines was examined. Interleukin (IL-6, IL-12B), and tumor necrosis factor (TNF)-α mRNA expression was significantly increased at 12–48 h after CDV infection. IL-10 mRNA expression was dramatically enhanced at 12–36 h after CDV infection. However, IL-4 and transforming growth factor (TGF-β) were not response to CDV infection. These results indicated that PBL differentiated intoCD4 + CD8 + T cells and improved the inflammatory response to CDV infection. Conclusions: After CDV infection, PBL differentiated into CD4 + CD8 + T cells and initiated inflammatory response. Highlights: In vitro antiviral test by infecting extracted peripheral blood lymphocytes from canine. Observation of canine peripheral blood lymphocytes infected with virus by laser scanning confocal microscopy. After CDV infection, peripheral blood lymphocytes differentiated into CD4 + CD8 + T cells and triggered an inflammatory response.